A pilot study to show that asymptomatic sexually transmitted infections alter the foreskin epithelial proteome - Chigorimbo-Murefu, Nyaradzo T. L.; Potgieter, Matthys; Dzanibe, Sonwabile; Gabazana, Zikhona; Buri, Gershom; Chawla, Aditya; Nleya, Bokani; Olivier, Abraham J.; Harryparsad, Rushil; Calder, Bridget; Garnett, Shaun; Maziya, Lungile; et al. (Frontiers in Microbiology, 2022)
There is limited data on the role of asymptomatic STIs (aSTIs) on the risk of HIV acquisition in the male genital tract. The impact of foreskin removal on lowering HIV acquisition is well described, but molecular events leading to HIV acquisition are unclear. Here in this pilot study, we show that an asymptomatic urethral infection with Chlamydia trachomatis significantly impacts the foreskin proteome composition. We developed and optimised a shotgun liquid chromatography coupled tandem mass spectrometry-based proteomics approach and utilized this on foreskins collected at medical male circumcision from 16 aSTI+ men and 10 age-matched STI- controls. We used a novel bioinformatic metaproteomic pipeline to detect differentially expressed proteins. Gene enrichment ontology analysis revealed proteins associated with inflammatory and immune activation function in both inner and outer foreskin from men with an aSTI. Neutrophil activation/degranulation and viral-evasion proteins were significantly enriched in foreskins from men with aSTI whereas homotypic cell-cell adhesion proteins were enriched in foreskin tissue from men without an aSTI. Collectively, our data shows that asymptomatic urethral sexually transmitted infections result in profound alterations in epithelial tissue that is associated with depletion of barrier integrity and immune activation.